Hypolipidemic activity of Coriandrum sativum in diabetic dyslipidemic rats - Das, Sayan; Rajadnya, Vikram; Kothari, Revati; Tilak, A. V.; Raveendran, Siddhi; Deshpande, Teja (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Metabolic syndrome is described as the clustering of obesity, aberrant glucose metabolism, dyslipidemia and hypertension. A characteristic pattern, termed diabetic dyslipidemia, consists of low HDL, increased triglycerides and postprandial lipemia. This pattern is most frequently seen in type 2 diabetes and may be a treatable risk factor for subsequent cardiovascular disease. This study was designed to compare the hypolipidemic activity of Coriandrum sativum L. with the standard antidiabetic drug, metformin in streptozotocin induced diabetic rats. Methods: Streptozotocin (STZ) was used to induce diabetes in the rats. The hypolipidemic activity of Coriandrum sativum seed extract was compared to the standard drug metformin. 4 groups (n=8) (normal control, diabetic control, streptozotocin+Coriandrum sativum and streptozotocin+metformin). The drugs were administered once daily for 28 days following which lipid profile was estimated on 28th day by using blood sample collected from the retro-orbital space. Results: STZ induced diabetes and also lead to dyslipidemia. Oral administration of CS seed extracts significantly lowered total cholesterol (TC), LDL:HDL ratio, TC:HDL ratio, thus, reducing the cardiovascular risk. HDL levels were slightly increased with CS seed extract compared to diabetic control group but not statistically significant. There was also statistically insignificant reduction in the atherogenic index with CS seed extract compared to diabetic control. Conclusions: CS seed extract (40 mg/kg) orally may have considerable therapeutic benefit as a hypolipidemic agent and can be suggested as a potential dietary add on.